The client side of everyday corruption in Central and Eastern Europe: the case of Chinese migrant entrepreneurs in Romania - Hiah, Jing (European journal of criminology, 2020)
This article provides an in-depth understanding of the corruption experiences of migrant entrepreneurs in transition economies. Drawing from ethnographic research, including 50 qualitative interviews with Chinese migrant entrepreneurs active in wholesale markets, non-governmental organizations, and supervisory agencies in Romania, this article demonstrates that normalization of corruption by migrant entrepreneurs should be understood in the historical context of the wholesale market as a product of post-1989 transition in Central and Eastern Europe. At a social-interactional level, normalization of corruption is revealed through how migrants use decriminalizing language to refer to corruption and perceive corruption as a survival strategy by public officials. Moreover, the legal and outsider status of migrants and their knowledge of the language, rules and laws further determine migrants’ position as clients of ‘on the spot’ corruption.